Alyssum doerfleri Degen (Brassicaceae), new for the Italian flora - Bernardo, Liliana; Maiorca, Giovanni; Roma-Marzio, Francesco; Peruzzi, Lorenzo (Phytotaxa, 2018)
Alyssum doerfleri is recorded for the first time in Italy from Monte Sellaro, Pollino National Park (southern Apennines, Calabria). Macro- and micro-morphology (including SEM study of trichomes) and karyology (2n = 16) of the Italian plants are congruent with the data available for Balkan populations. Chorological and conservation features of this species are presented and discussed.